Design And Development Of Arduino-Based Smart Classroom System - Michella Monica; Alfa Satya Putra (STMIK PONTIANAK, 2021)
The purpose of this research is to design and develop a Smart Classroom system. The system is expected to minimize academic dishonesty in attendance and assignment submission. A survey about academic dishonesty was distributed to 144 university students and lecturers to measure the level of academic dishonesty. Survey result shows that 54.5% of students surveyed has committed academic dishonesty, and 60% of lecturers surveyed has discovered academic dishonesty incidents. Furthermore, 55.2% of students and 20% of lecturers surveyed believed that the attendance system used is not effective, which causes academic dishonesty cases. Thus, a Smart Classroom system was developed using fingerprint scanner module to take attendance and QR barcode scanner to take assignment submission. The system is controlled using Arduino Mega 2560 microcontroller board and includes database and website to manage and display data. System testing shows that success rate of fingerprint scanner module in taking attendance is 90%, and success rate of QR barcode scanner module in assignment submission is 100%.